2013
DOI: 10.1002/gbc.20025
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for elevated emissions from high‐latitude wetlands contributing to high atmospheric CH4concentration in the early Holocene

Abstract: [1] The major increase in atmospheric methane (CH 4 ) concentration during the last glacial-interglacial transition provides a useful example for understanding the interactions and feedbacks among Earth's climate, biosphere carbon cycling, and atmospheric chemistry. However, the causes of CH 4 doubling during the last deglaciation are still uncertain and debated. Although the ice-core data consistently suggest a dominant contribution from northern high-latitude wetlands in the early Holocene, identifying the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…For the Holocene, several authors have suggested higher CH 4 emissions from high-latitude ecosystems relative to the LGM (71)(72)(73). Based on pollen analyses, Yu et al (73) proposed a protopeatland phase as the precursor for the succession from wetlands to fens and later bogs.…”
Section: Discussionmentioning
confidence: 99%
“…For the Holocene, several authors have suggested higher CH 4 emissions from high-latitude ecosystems relative to the LGM (71)(72)(73). Based on pollen analyses, Yu et al (73) proposed a protopeatland phase as the precursor for the succession from wetlands to fens and later bogs.…”
Section: Discussionmentioning
confidence: 99%
“…1e). We argue that Sphagnum spores approach likely underestimates the extent of peatlands in the early Holocene, at which time peatlands (mostly rich fens) were often dominated by nonSphagnum plants (Gajewski et al, 2001;MacDonald et al, 2006;Yu, 2011;Yu et al, 2012b). Gorham (1991) also indicated that northern peatlands accumulate their carbon mostly in the late half of the Holocene.…”
Section: Peatland Changes Over Timementioning
confidence: 92%
“…1b) using the 1516 basal peat ages across the northern peatland domain (Fig. 1a;MacDonald et al, 2006), under the assumption that the expansion rates of individual peatlands were constant, or peatland area has increased linearly, since their peatland Gorham et al, 2007;and Korhola et al, 2010 as in Yu et al, 2012b); (B) peatland area change at 1000-yr intervals over time estimated from cumulative basal age histogram as in (A) (MacDonald et al, 2006) and the present peatland area of 4 × 10 6 km 2 (Yu, 2011); (C) carbon accumulation rates based on 33 sites across northern peatlands with error bars from standard errors of the means (Yu et al, 2009); (D) observed net carbon pool (NCP) and modeled net carbon balance (NCB) for northern peatlands at 1000-yr intervals, with standard errors as error bars Yu, 2011); (E) cumulative peatland carbon stocks from NCP (squares; Yu et al, 2010), NCB (circles), and from scaling the carbon stocks of Gorham (1991) using Sphagnum-spore data (Gajewski et al, 2001). Sheng et al (2004) initiation and formation Yu, 2011).…”
Section: Approach Equation Example Notementioning
confidence: 99%
“…These ecosystems are therefore unique components of the global C cycle, and consequently of the global climate, especially on longer time scales. Over the Holocene, peatland development and expansion has had an impact on the atmospheric CO 2 and has also contributed to increasing atmospheric methane (CH 4 ) concentrations (Macdonald et al 2006;Yu et al 2013). …”
Section: Introductionmentioning
confidence: 99%